Celiac arteriography - Silva García, Ernesto (Cirugía del Uruguay, 1973)
The paper shows the value of arteriography of the celiac axis in portal hypertension, benign and nalign expansive processes, thoracoabdominal traumatism and in testing the permeability of the splenoportal venous axis when there are doubts as to classic splenóportography.